2013
DOI: 10.1159/000347220
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Quality of Life for Poor Prognosis Stage 5D Chronic Kidney Disease with and without Dialysis

Abstract: Background: Renal replacement therapy (RRT) has not always been shown to benefit end-stage renal failure patients who are elderly or have multiple comorbidities in terms of survival or symptom control. Conservative management may be a viable alternative offering comparable health-related quality of life. Methods: This is a prospective observational study of 101 patients who reached an estimated glomerular filtration rate of 8-12 ml/min and were either ≥75 years old or had an age-adjusted Charlson Comorbidity I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 37 publications
6
84
2
2
Order By: Relevance
“…QoL was maintained during the 3-year follow-up period in patients on CKM and patients on HD, except for life satisfaction, which declined after starting dialysis in the HD group. Similar outcomes have been reported in other observational studies (20).…”
supporting
confidence: 91%
“…QoL was maintained during the 3-year follow-up period in patients on CKM and patients on HD, except for life satisfaction, which declined after starting dialysis in the HD group. Similar outcomes have been reported in other observational studies (20).…”
supporting
confidence: 91%
“…Neither of these latter two studies provided the eGFR of the patients in the conservative care groups. A study from Singapore, where all patients have to pay for dialysis treatments, suggested that QoL was similar for older and multiply comorbid patients on conservative care compared with those on dialysis, but the burden of kidney disease is higher in the dialysis group [28]. However, this study could be confounded by social and financial differences between the groups.…”
Section: Discussionmentioning
confidence: 87%
“…Others had a combination of individuals undergoing hemodialysis and peritoneal dialysis (n = 5, 21%) and individuals undergoing hemodialysis and kidney transplantation (n = 2, 8%) . One publication did not define the type of RRT …”
Section: Resultsmentioning
confidence: 99%